TASAMUH SEBAGAI NILAI PENDIDIKAN DALAM PEMIKIRAN TGKH. MUHAMMAD ZAINUDDIN ABDUL MADJID DAN RELEVANSINYA DI SD - Adet Tamula Anugrah (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to analyze the thought of TGKH. Muhammad Zainuddin Abdul Madjid on tasamuh (tolerance) and to explore its relevance to primary education in Indonesia. Employing a qualitative approach, this research is conducted through a literature study by examining his work, Wasiat Renungan Masa Pengalaman Baru. The findings reveal that tasamuh in the perspective of TGKH. Muhammad Zainuddin Abdul Madjid is not merely limited to the acknowledgment of differences but rather constitutes a civilizational framework encompassing four dimensions: moral foundation (self-control), social practice (solidarity and mutual cooperation), spiritual-ethical prerequisite (kindness and compassion), and social outcome (unity and communal stability). The relevance of this thought to primary education lies in its contribution to achieving the objectives of Article 3 of the Indonesian National Education System Act, particularly in strengthening students’ self-control, noble character, and social competence. Thus, the concept of tasamuh as formulated by TGKH. Muhammad Zainuddin Abdul Madjid can be positioned as a contextual and applicable model of character education in addressing contemporary challenges in primary education, including bullying, exclusivism, and respect for diversity.